SPE/DOE Symposium on Improved Oil Recovery 2006
DOI: 10.2118/100082-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Chemical Flooding in a Mixed-Wet Dolomite Reservoir

Abstract: Many pilot tests and several commercial field projects have been performed over the past few decades and have shown that surfactant/polymer and alkaline/surfactant/polymer floods can recovery high percentages of residual oil saturation. However, these chemical processes are sensitive to parameters such as chemical slug size and concentrations, salinity, reservoir heterogeniety and surfactant adsorption among other key parameters. In this study, a sensitivity analysis of these key parameters was performed to op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…In 1978, a 1-D numerical simulator was developed by Pope and Nelson [21] to describe surfactant enhanced oil recovery and it has been extended to other chemical processes and to 3-D as UT-CHEM [22][23][24]. Furthermore, ECLIPSE, which is a commercial reservoir simulator, was developed by Schlumberger.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…In 1978, a 1-D numerical simulator was developed by Pope and Nelson [21] to describe surfactant enhanced oil recovery and it has been extended to other chemical processes and to 3-D as UT-CHEM [22][23][24]. Furthermore, ECLIPSE, which is a commercial reservoir simulator, was developed by Schlumberger.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…More recent field applications used 0.5 PV as a starting slug size and then adjust it based on performance and economic considerations. Anderson et al (2006) suggested that slugs greater than 0.5 PV have little effect and indicated the need for buffers to avoid slug disintegration. For this exercise, 0.4 PV is compared with continuous injection of polymer.…”
Section: Slug Sizementioning
confidence: 99%
“…Gharbi (2001) suggested 2800 ppm was an optimum polymer concentration in an Alkaline-Surfactant-Polymer flood design. Anderson et al (2006) used values between 1000 and 2000 ppm in a surfactant-polymer flood. These two papers used oil price as the main selection criterion.…”
Section: Non-newtonian Parametermentioning
confidence: 99%
“…For these reasons, previous work has been limited to lab-scale optimization and field-scale sensitivity studies (Zerpa et al, 2005). For instance, in Anderson et al (2006) a sensitivity study was undertaken to optimize a surfactant-polymer (SP) flood. To overcome computational costs, both Zerpa et al (2005) and Horowitz et al (2010) presented and tested surrogate-based optimization.…”
Section: Optimization Workflowsmentioning
confidence: 99%